Acute and repeated-dose toxicity of Echinops kebericho Mesfin essential oil - Deyno, Serawit; Tola, Mesfin Asefa; Bazira, Joel; Makonnen, Eyasu; Alele, Paul E. (Toxicology Reports, 2021)
Echinops kebericho Mesfin is used for the management of various diseases and fumigation during child birth. This study investigated acute and repeated-dose toxicity of E. kebericho M. essential oils (EOs). The study was conducted in Swiss albino mice. Organ weight, histopathology and clinical chemistry were analyzed. The dose and duration of treatment were defined in accordance with Organization for Economic Co-operation and Development (OECD) guideline. No mortality was observed in acute oral dose toxicity study up to 2000 mg/kg per body weight. Compared to control group, treated groups did not show significant abnormalities in body weight and most parameters of clinical chemistry parameters and relative organ weight in repeated-dose toxicity study. However, urea, albumin, aspartate aminotransferase, and relative organ weight of right kidney showed variations in treated groups compared to control group. All treated groups and control group showed normal histology except lymphocytic infiltrates observed on the kidney with 200 mg/kg treated female group. The current study revealed that EO of E. kebericho M. could be considered well tolerated in acute and repeated-dose exposure. Further, teratogenic, mutagenic, carcinogenic, and sub-chronic and chronic toxicity studies are warranted.
Keywords: Safety; Herbal medicine; Clinical chemistry; Histopathology